Development of digital map: Case study of Bandaraya Alor Star - Kiong, Siew Wai; Ahmad, Amran; Zainal Abidin, Ahmad Hisham (2006)
Nowadays, Web is considered as a common tool to share information on the Internet.With the advent of Web Services, many organizations used it as a medium to integrate inter-enterprise application across the Internet. Moreover, Web Services served as information distributor not only for business, entertainments, educations purposes, but also for local residents and tourists gather their information. The ability to view from different view is important in many current and future applications.The focus of this study is to design friendly interface of Digital Map of Alor Star city with the panoramic view for users to interact successfully in Virtual Reality (VR) Image-Based Environment. Besides that, usability testing conducted in this research reveals that the web base Digital Map application is effective to be implemented by the Bandaraya Alor Star in their Digital City application. From fifteen tasks performed by the participants, 100 percent of them are performed over the 70 percent of success criterion without asking for any assistance.